The Impact of Human Resources on the Rectorate of Universitas Hasanuddin Financial Performance - Khaeril Anwar Junaedi; Andi Ratna Sari Dewi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
The purpose of this study was to analyze and determine the influence and role of human resources on the quality of financial performance at the Rectorate of Accounting and Finance at Universitas Hasanuddin, Makassar. Quantitative research method with analysis using SPSS 25 and purposive sampling of 62 respondents. The results showed that the nature of responsibility and the provision of training to improve the quality of human resources had a positive and significant effect on the quality of financial performance, that roles and functions were varied, and that training materials tailored to the needs of financial staff played a key role in improving the quality of financial performance in the Rectorate of Accounting and Finance at Universitas Hasanuddin Makassar.